Utilization of foxtail millet (Setaria italica) and its processed forms on performance of broilers* - REDDY, P SUDHAKARA; NARAHARI, D (The Indian Journal of Animal Sciences, 2013)
Ground foxtail millet was incorporated at 0, 10, 20, 30 and 40% levels in experiment 1. In experiment 2 maize replaced with ground, genninated and pelleted foxtail millet each at 0,50 and 100 % levels, on isonitrogenous and isocaloric basis in broiler diets. The weight gain was in favour of 40% foxtail millet, but the feed intake and feed efficiency did not reveal any trend irrespective of the dietary levels of foxtail millet. Consequently insignificant variations were observed at 8 weeks of age. Pelleting of foxtail millet improved the perfonnance of broilers compared to mw, genninated, and maize-based diets. However, the weight gain was depressed with the total replacement of maize by germinated foxtail millet. The income over feed cost per bird was more or less directly ’proportional to the dietary level of raw and pelleted foxtail millet, but it was lower in genninated foxtail millet group. Ready-to cook yield, carcass protein and fat, haemoglobin, total serum protein and mortality were not affected by foxtail millet and its processed forms at any level.